Regulations on the Use of Indonesian in Making Contracts According to Indonesian Positive Law - Suwardiyati, Rumi; Rustam, Riky (Batulis Civil Law Review, 2024)
Introduction: Contracts form the backbone of business dealings, establishing the foundations and binding all collaborative endeavors between parties involved. In the Indonesian context, the use of the national language in contractual agreements has been explicitly governed by laws and regulations, specifically Law Number 24 of 2009 concerning the National Flag, Language, Emblem, and Anthem.Purposes of the Research: This study aims to scrutinize and analyze the regulatory framework surrounding the use of the Indonesian language in contract drafting, as mandated by the positive laws of Indonesia. Additionally, it seeks to elucidate the legal ramifications that may arise from non-compliance with these provisions. Furthermore, the research endeavors to provide legal clarity and offer recommendations pertaining to this issue.Methods of the Research: This research adopts a normative legal approach, employing both statutory and conceptual frameworks. The legal materials utilized encompass primary, secondary, and tertiary sources. The collection of legal materials is facilitated through library research, while the analysis of these materials is conducted qualitatively, employing content analysis and legal interpretation techniques.Results of the Research: The findings of this research present a comprehensive analysis of the regulations governing the use of the Indonesian language in contract drafting, shedding light on the legal implications of non-compliance with these provisions. Furthermore, the research offers recommendations and suggestions tailored for government agencies, business entities, and legal practitioners, guiding them in implementing the use of the Indonesian language in contracts in accordance with the applicable legal framework.